Social representations of sexual health: encounters and disencounters in HIV testing - Figueroa Varela, Ma. del Rocío; Herrera Herrera, Miguel Ángel (Acta Universitaria, 2022)
The purpose of the study was to analyze differences of content and structure in social representations of sexual health among young men and women who had already applied (or not) HIV tests. Through an intentional random sampling, the technique of hierarchical evocation was applied to 204 young people between the ages of 18 and 29, in the city of Tepic, Nayarit, México. An analysis of importance and frequency was done to identify the structure of the representation, as well as a categorization for theoretical areas to classify its content. For young people who had not applied HIV tests, sexual health was understood through biomedical references with a focus on responsibility, whereas those who had applied the diagnosis test added meanings related to affect and self-care. The results are discussed in terms of their articulation with the socio-cultural system of gender, sexuality, and health.